2011
DOI: 10.1016/j.biomaterials.2011.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Redox-responsive nanocapsules for intracellular protein delivery

Abstract: Proteins play a crucial role in life, taking part in all vital processes in the body. Intracellular protein delivery holds enormous promise for biological and medical applications, including cancer therapy, vaccination, regenerative medicine, treatment for loss-of-function genetic diseases and imaging. Engineering vehicles for escorting therapeutic proteins into specific cells in a controlled release fashion has thus generated considerable interest. The development of such therapeutics to selectively target tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 109 publications
(110 reference statements)
0
137
0
Order By: Relevance
“…Zhao et al reported the preparation of redox-responsive single-protein nanocapsules for intracellular protein delivery [49]. In this delivery system, target protein was non-covalently encapsulated into a positively-charged polymeric shell interconnected by disulfide-containing crosslinkers via in situ interfacial polymerization.…”
Section: Physiological Stimuli-triggered Deliverymentioning
confidence: 99%
“…Zhao et al reported the preparation of redox-responsive single-protein nanocapsules for intracellular protein delivery [49]. In this delivery system, target protein was non-covalently encapsulated into a positively-charged polymeric shell interconnected by disulfide-containing crosslinkers via in situ interfacial polymerization.…”
Section: Physiological Stimuli-triggered Deliverymentioning
confidence: 99%
“…Most developed intracellular releasing nanocarriers are responsive to either pH [ 7 , 8 ] or redox potential. [ 9 ] Recently, we designed a new type of polymer, poly[(2-(pyridin-2-yldisulfanyl)-co-[poly(ethylene glycol)]] (PDSEG), containing both ester and disulfi de bonds, which are labile to acidic pH and redox potential, respectively. PDSEG polymer contains both hydrophilic polyethylene glycol segments and hydrophobic pyridyl disulfi de segments.…”
Section: Doi: 101002/adma201202687mentioning
confidence: 99%
“…Within the fields of gene therapy and RNA interference, the challenge of targeted intracellular delivery is well appreciated (2,3); the same is true for protein therapeutics (4,5). The delivery of protein antigens to the intracellular compartment of antigen presenting cells is also enhanced by various mechanisms of endosomal disruption (6,7).…”
Section: Introductionmentioning
confidence: 99%